Technology Management in Banks: An Empirical Study with Special Reference to State Bank of India - Narasimha Rao, V. (Prabandhan: Indian Journal of Management, 2013)
The Banking sector is undoubtedly the prime catalyst for economic growth in any country. The key drivers of sea change in banking operations in India are integration of financial markets across the globe, explosion of information and communication technology and management of knowledge. The benefits of technology in Indian banks are quite well known. Banking in India started in the year 1786, with the General Bank of India being the first one. Reserve Bank of India came in 1935 and became the central banking authority in 1965. Prior to the 1990's, the diffusion of Information and Communication Technology (ICT) in the Indian banking industry was mainly on operations, but from the mid 1990's, the use of technology is present in external environment i.e. in products or service offerings to customers. It is to be understood that IT is not yet a very comfortable choice for millions and consumer awareness is a major challenge in our country. State Bank of India, the premier and the largest commercial bank in the country with a market share of 17% for advances, and 17.98% for deposits is well positioned to capture growth in the dynamic Indian banking market, and is seen as a macro-economic proxy for the Indian economy. SBI is going through a momentous phase of its technology management. The Indian banks have nevertheless, withstood all the challenges at the national and international level and are becoming more adaptive to the changing environment. Technology management is essential for the banking sector in today's knowledge economy. The ultimate objective of using technology in banks should be increasing service quality and thereby enhancing customers' satisfaction. This paper is an attempt to understand technology management in banks with special reference to State Bank of India.